2013
DOI: 10.1136/emermed-2013-202660
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the activity and impact of emergency care practioners in the NHS

Abstract: Successful implementation of the ECP role has been described. Further evaluations should consider whether the beneficial impact of the role transfers equally across all operational settings and patient groups, and is not just a reflection of new investment in clinical services.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(26 citation statements)
references
References 22 publications
2
24
0
Order By: Relevance
“…We have summarised the characteristics and findings of the seven systematic reviews [146][147][148][149][150][151]173 (Tables 10 and 11). Data on the 12 papers 174-185 not included in the systematic reviews were extracted in to summary tables (Tables 12-14).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have summarised the characteristics and findings of the seven systematic reviews [146][147][148][149][150][151]173 (Tables 10 and 11). Data on the 12 papers 174-185 not included in the systematic reviews were extracted in to summary tables (Tables 12-14).…”
Section: Resultsmentioning
confidence: 99%
“…Six of the systematic reviews [146][147][148]150,151,187 found evidence that prehospital professionals can successfully reduce the number of patients transported to EDs and provide autonomous care and appropriate referral in the community setting. The evidence is predominated by schemes to provide ambulance paramedics with extended and enhanced clinical skills.…”
Section: Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…The available evidence indicates that specialist roles have reduced conveyance to ED and increased discharge at scene, thus reducing the costs associated with ambulance journeys, ED attendances and hospital admissions. 10,11 However, one of these reviews also concluded that there is a lack of rigorous evidence on the appropriateness of decisions and the safety of patients. 11 The need for a better understanding of influences on the safety of paramedic decision making and potential risk factors (threats) is particularly important in the context of plans to develop emergency ambulances into mobile urgent treatment services capable of dealing with more people at scene, 5 to ensure that such developments do not increase the risk for patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, this higher level of education and training represents a minority of paramedics. There is some evidence that ECPs can deliver quality care safely 75 and are having an impact on non-conveyance rates, with discharge rates upward of 20% greater than those for usual care, 6,76,77 although the evidence for subsequent readmission or appropriateness of care is generally lacking.…”
Section: Staff Roles Skills and Developmentmentioning
confidence: 99%